Beyond the borderline: Outcomes for inborn infants born at ≤500 grams. (6th October 2013) - Keir, Amy; McPhee, Andrew; Wilkinson, Dominic
<x xml:space="preserve">Abstract</x> Aim To report survival, morbidity and neurodevelopmental outcome in a cohort of extremely low birthweight infants. Methods Retrospective cohort study of all inborn infants born alive with birthweights ≤500 g ≥22 weeks gestation at Women's and Children's Hospital, Adelaide, Australia, over a 6‐year period (2005–2010). Outcome data including standardised medical and psychological assessments at 12 and 36 months corrected age were collated from follow‐up. Results A total of 36 eligible infants were born over the study period (mean gestational age (GA) 24.4 (range 22.0–30.0) weeks; birthweight 443 (330–500) grams). Twenty‐six of the 36 (72%) infants were small for gestational age (SGA).Ten of the 36 infants received compassionate care and died in the delivery or operating room. Twenty‐six of the 36 infants were admitted to the neonatal intensive care unit (NICU), of whom 12 (46%) died during their admission. At age 12 months corrected, 2/14 (14%) of survivors had none/minimal, 4/14 (29%) had mild and 8/14 (57%) had moderate/severe neurodevelopmental disability. Overall, the survival rate was 39%, and survival without neurodevelopmental disability was 6%. Only 1/10 appropriate‐for‐gestational‐age (AGA) infants survived to discharge (and had severe disability), whereas 13/26 (50%) of all SGA infants in the study survived to discharge. Of all infants admitted to the NICU, 11/26 (42%) survived without severe neurodevelopmental disability at latest follow‐up. Conclusions There was a high risk of death or impairment in this cohort of infants. Survival was rare for AGA infants weighing ≤500 g at birth. Our study provides an evidence base to assist counselling and decision‐making.